Learning in Struggle: Argentina’s New Worker Cooperatives as Transformative Learning Organizations - Vieta, Marcelo (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2014)
SummaryThis article considers Argentina’s empresas recuperadas por sus trabajadores (worker-recuperated enterprises, or ERTs) as transformative learning organizations. ERTs are illustrative of how workers’ conversions of capitalist firms into worker cooperatives—especially conversions emerging from troubled firms and in moments of deep socio-economic crises—transform workers (from managed employees to self-managed workers), work organizations (from capitalist businesses to labour-managed firms), and communities (from depleted to revitalized and self-provisioning localities).Theoretically, the study is grounded in class-struggle, workplace learning, and social action learning approaches. These theoretical perspectives help the study work through how workplace conversions by workers, when converting troubled investor-owned or proprietary firms into worker coops, act as catalysts for contesting workplace exploitation and capitalist crises, while also beginning to move beyond them by forging new social relations of production and exchange. In the case of Argentina’s ERTs, crises in the political economy and micro-economic crises at the point of production during the collapse of the neoliberal model at the turn of the millennium heightened workers’ self-awareness of their situations of exploitation and motivated collective action. As a result, new worker cooperatives were created that also stimulated the social, cultural, and economic renewal of surrounding communities.The study’s research method relies on extended case studies of four diverse ERTs, which included ethnographic observation and in-depth interviews. Observations of daily workflows were conducted, as well as interviews and informal conversations with founding and newer ERT workers. In a more structured portion of the interview protocol, key-informants were asked to reflect on how they had personally changed after being involved in the ERT, and how production practices and involvement with the community had transformed in the process of conversion.The article concludes by outlining how worker, organizational, and community transformations emerge from workers’ processes of informal learning and learning in struggle as they collectively strive to overcome macro- and micro-economic crises and learn to become cooperators. This learning, the study shows, occurs in two ways: intra-cooperatively via informal workplace learning, and inter-cooperatively between workers from different ERTs and with surrounding communities. The self-management forged by ERTs thus embodies new, cooperative, and community-centered values and practices for these workers that, in turn, sketch out different possibilities for economic and productive life in Argentina.